Euroregional Multifunctionality and its Importance in the Activation of Border Areas - Marianna Greta; Jacek Otto (Comparative Economic Research. Central and Eastern Europe, 2019)
The study deals with the problems of Euroregions in the context of their multifunctionality. Multifunctionality is presented by analyzing the institutional structure and objectives pursued. The institutional structure presents the functions of individual Euroregional institutions and the importance of the Association of European Border Regions (AEBR) as the superior representation of Euroregions. Referring to the objectives, they are presented in the light of the theoretical assumptions adopted for this type of structure, emphasizing that in their implementation there is a "hidden" multifunctionality of the Euroregion. In addition, the implementation of the objectives was verified in practice on the example of direct empirical research carried out in selected Polish Euroregions just after their creation and from the perspective of them operating for several years. Positive opinions in this respect, which prevail as integration awareness and the maturation of the Euroregion increases, support the establishment of such structures and verify their importance for the activation of border areas.
Keywords: F15; R11; 330; European integration; region and regional policy; Euroregion